Die- back in cashew incited by the Tea Mosquito Bug, Helopeltis antonii Signoret as influenced by wound pathogens and plant biochemicals - Bindu N (Department of Agricultural Entomology, College of Horticulture, 1996)
Experiments were conducted at the College of Horticulture, Vellanikkara and in the cashew fields at Cashew Research Station, Madakkathara, to ascertain the intensity of shoot die-back symptoms in cashew incited by the TMB bug, Helopeltis antonii in association with the wound pathogens; to evaluate the selected plant products for their feeding detterrency to TMB; to study the variations in the major biochemical factors such as starch, sugars, phenol and OD phenol in the five susceptible and five less susceptible cashew types and the changes in these biochemical factors due to TMB feeding. The predominantly occurring fungus isolated from the necrotic lesions of the TMB affected shoots, panicles and nuts was Colletotrichum gloeosporioides. The involvement of the fungus in the die-back symptom development calls for appropriate modifications in the crop protection strategies particularly for younger cashew plantations. The necessary strategic shifts have been discussed. The role of this fungus in aggravating the seedling die-back when inoculated on the grafts infested by TMB has been established. Emulsions of neem and pongamia oil at 2 per cent and 5 per cent spray caused mortality of adult bug after 12 h of exposure. Significant variations in the biochemical constituents viz., starch, sugar, phenol and OD phenol content were detected in all the ten cashew accessions. Comparatively low starch content was noticed in most of the susceptible cashew types and high in the less susceptible type. The starch content increased during the 6 h followed by significant decrease during 12 and 24 h of infestation by TMB. Low sugar content was found in the less susceptible accessions. The sugar content showed significant decrease during 6,12 and 24 h of infestation by TMB. The phenol and OD phenol contents were lower in the susceptible cashew accessions than the less susceptible accessions. The phenol content showed an increasing trend at 6 h followed by a decrease during 12 h and again an increase during 24 h of infestation by TMB. The varietal variations and the time interval after the TMB infestation seemed to influence the rate of biochemical reaction rather than any specific biochemical changes induced by the interaction of varieties and TMB feeding.